A Photoresponsive Battery Based on a Redox‐Coupled Covalent‐Organic‐Framework Hybrid Photoelectrochemical Cathode. Issue 50 (17th November 2022) - Wang, Wei; Zhang, Xiang; Lin, Jing; Zhu, Lei; Zhou, Enbo; Feng, Yangyang; Yuan, Daqiang; Wang, Yaobing
Abstract: Photoresponsive batteries promise flexible and low‐cost solar‐to‐electrochemical energy storage (SES), but suffer from a limited SES efficiency due to rapid charge recombination and sluggish redox. Here, we present a porous‐shell/core hybrid of covalent organic framework@carbon nanotube. This hybrid ensures long‐lived separated charges (τave =3.0 ns) by an electron transfer relay starting from the donor‐acceptor molecules to the nanoscale heterojunction. These charges are further allowed to drive high‐rate redox of −C=O/−C−O − and −C−N/−C=N + with facile kinetics. Equipped with this photoelectrochemical cathode, a photoresponsive aqueous battery shows a 5‐fold enhancement in SES efficiency (1.1 % at 1 sun) over their counterparts. It is unveiled that the electron relay favors the formation of electron‐enriching −C−O− and hole‐enriching −C=N + groups responsible for photoelectrochemical Zn 2+ and OTf − storage cascade; and further, the general photo coupled ions transfer (PCIT) process is proposed. This work presents an inspiring photoelectrochemical cathode design and theoretical insight for photoresponsive batteries. Abstract : A porous‐shell/core hybrid (TN‐COF@CNT) enables a long‐range charge transfer relay and a high‐rate dual‐redox for the realization of efficient photo coupled ions transfer process. Equipped with such a photoelectrochemical cathode, a photoresponsive aqueous battery achieves reliable photoresponses, enhanced battery efficiency, stability and a remarkable solar‐to‐electrochemical energy storage efficiency of 1.1 %.